Faktor-faktor yang Mempengaruhi Pengungkapan Sukarela “Internet Financial and Sustainability Reporting” - Luciana Spica Almilia (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2008)
Internet Financial and Sustainability Reporting (IFSR) is voluntary in nature. With no specific regulations on IFSR, there is a disparity of IFSR practices among companies. Some companies disclose only partial financial statement using a low level of technology, while others disclose full sets of financial reports using sophistications of the web such as multimedia and analytical tools. SustainAbility (1999) addressed the benefits (global reach, immediacy, ease of updating, transparency, link ability, and interactivity) of reporting social and environmental information on the website and thus the factors that affect decision of whether or not to use this communication medium. By placing information on the firm’s website, users can search, filter, retrieve, download, and even reconfigure such information at low cost in a timely fashion.The purpose of this study was to examine financial variables that affect Internet Financial and Sustainability Reporting (IFSR) in Indonesia Stock Exchange companies. The samples of this research include 104 listed firms in Indonesia Stock Exchange. The multiple regressions was used to examine variables that affect Internet Financial and Sustainability Reporting (IFSR). The sample of this research is companies that listed in Indonesia Stock Exchange companies. The findings of this research found that firm size, return on asset, and majority holder are determinant factors of IFSR index in Indonesia.Keywords: internet, internet sustainability reporting, internet financial reporting, company website